Food Security And Performance Of Rice Agribusiness Institutions In Coastal Areas Of Seluma Regency - Sriyoto Sriyoto; Irnad Irnad; Bambang Sumantri; Basuki Sigit Priyono (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
Food security in Indonesia has become a central issue inagricultural development and national development. Theproblem of food and food security cannot be separated fromthe context of rice. This is because rice is a staple foodconsumed by almost all Indonesians. Thus, the availabilityof rice is an important factor in strengthening national foodsecurity. The level of national food security, regional foodsecurity must be followed by the achievement of the level ofresilience of villages, households and individuals. The roleand performance of rice agribusiness institutions areimportant in the effort to achieve household food securityfor rice farmers. The objectives of this research are: 1) toanalyze the food security level of farmers household; 2) toidentify the determinants of food security level; 3) identifyingthe level of food security with the institutional performanceof rice agribusiness. The results of this study indicate that thelevel of household food security is categorized as foodresistance, the determinants of the level of food security areinfluenced by the number of family members and theincome of rice farming. The food resistance category wasfollowed by the institutional performance of PT. Pusri is verygood, PT. Pertani is good, Bank of BRI is good, and farmergroup institutions are moderate.